(3eNGWQ GdCef GdeGFj GdYQHj h NjGQGJ GdJfejI GdeGFjI ddbQf GdMGOj YTQjf (B/s - (3GdWhjd, QhGA Rcj jhfSs ((3YfGJ(B: s (3OGQ RgQGf(B, s, 2009)
(3CgejI GdGef GdeGFj GdYQHj h CKQg Ydi GdGef GdZPGFj GdYQHj h GdJHYjI GdGbJUGOjI h GdZPGFjI h HGdJGdj eNGWQg Ydi GdGef Gdbhej GdYQHj , HjGf CgejI JfejI GdehGQO GdeGFjI GdMGdjI h GdJfHjg dNWhQI GdJUMQ (B.s
(3eQGLY U(B.122s
Keywords: (3GdGef GdZPGFjs; (3GdCef Gdbhej(B- (3GdHdOGf GdYQHjIs; (3GdJHYjI GdEbJUGOjIs